Membangkitkan Kepedulian Lingkungan Melalui Program SEKARDADU di Daerah Aliran Sungai (DAS) Desa Bedewang – Songgon – Banyuwangi - Fajri Andi Rahmawan; Laili, Roudlotun Nurul; Muhammad Al Amin; Muhammad Nashir; Hirdes Harlan; Akhmad Yanuar Fahmi; Ali Syahbana; Erik Toga; Ivan Rachmawan; Dian Roshanti (Jurnal Nusantara Berbakti, 2023)
Environmental problems, especially rivers, have become a global issue that must receive more attention because of their extraordinary impact on society. Some residents of Bedewang village still use the river for bathing, defecating and washing. However, ironically, most people are apathetic and care less about preserving the river, where residential waste is the biggest contributor to river pollution because they throw away kitchen waste, leftover food and diapers around the watershed. This Community Service activity aimed to increase public awareness of the environment through the SEKARDADU program in the Bedewang Watershed, Songgon - Banyuwangi. The methods used include socialization, providing education, and direct assistance. The activity results showed that residents can directly implement the socialization/education activities provided, the understanding of using clean water for daily needs and forming a community commitment to preserving the river so that disasters do not occur due to environmental damage.